Combined Application of Immunohistochemistry and Warthin-Starry Silver Stain on the Pathologic Diagnosis of Cat Scratch Disease. Issue 10 (November 2020) - Peng, Jinwu; Fan, Zhuoyang; Zheng, Hongmei; Lu, Junmi; Zhan, Yuting
Abstract : Purpose: Cat scratch disease (CSD) is an infectious disorder caused primarily by the bacterium Bartonella henselae (B. henselae) . Immunohistochemistry (IHC) and Warthin-Starry silver stain (WS) are considered to be indispensable to diagnose CSD in combination with morphologic characteristics. In this study, we retrieved and reviewed 46 cases of paraffin-embedded lymphadenitis with histologic and/or clinical suspicion of CSD between 2014 and 2018, and detected B. henselae by IHC and WS, respectively, and evaluated the application significance of IHC and WS for the detection of B. henselae and validated their values in the pathologic diagnosis of CSD. Materials and Methods: B. henselae was detected by IHC and WS; validation of 2 methods for detecting B. henselae was evaluated by sensitivity, specificity, false-positive rate, false-negative rate, precision, negative predictive value, and agreement rate. Results: Microscopically, suppurative granulomas and/or multiple stellate microabscesses were observed in the accessory cortex of lymph nodes, especially near the subcapsule. Our results showed that 80.4% (37/46) of cases were positive for B. henselae by IHC, manifesting mainly punctuate, granular, or linear to outline the shape of bacteria. However, the positive rate of B. henselae by the WS method was 52.2% (24/46). There was a significant difference between IHC and WS ( P =0.023). Moreover, a positive percentage of B. henselae was 97.8% (45/46), which was detected by the combined application of IHC and WS. The combination of IHC and WS exhibited high sensitivity (97.8%) and good agreement rate (86.5%). Conclusion: The combined application of the IHC and WS method may have important clinical advantages, which is with the highest sensitivity and agreement rate for pathologic diagnosis of CSD.